Exaggeration principle for CGI character visualization: A framework for Panglima Bukit Sadok / Goh Kiang Kuan - Goh , Kiang Kuan (2017)
This research gave focus to study exaggeration principle which already proven internationally by many well-known animation studios to be the key for the success of stylized CGI character visualization. Even though many existing literary works introduced and recommended the implementation of exaggeration principle in character design development, but apparently, there is no literary work that offers a comprehensive documentation, knowledge and insights to describe specifically on the methodology of how exaggeration principle could be implemented with the relevant visual attributes and how it could be linked to others animation principles in the development process of CGI character visualization. In align with this study, the researcher had adopted his existing practical project of 2013, CGI character of Panglima Bukit Sadok as the case study. The researcher made an effort to study from the CGI character visualization industry experts in order to obtain a special kind of information within the scope of area. This study approach is aimed to develop a set of framework as a guide to aid the problem resolving process of Panglima Bukit Sadok CGI character visualization. Ultimately, this framework could also serve as one of the useful references for any practitioners as well as inspires future research on the development of local CGI character visualization.